2023
DOI: 10.1038/s41598-023-48953-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel feature selection algorithm for identifying hub genes in lung cancer

Tehnan I. A. Mohamed,
Absalom E. Ezugwu,
Jean Vincent Fonou-Dombeu
et al.

Abstract: Lung cancer, a life-threatening disease primarily affecting lung tissue, remains a significant contributor to mortality in both developed and developing nations. Accurate biomarker identification is imperative for effective cancer diagnosis and therapeutic strategies. This study introduces the Voting-Based Enhanced Binary Ebola Optimization Search Algorithm (VBEOSA), an innovative ensemble-based approach combining binary optimization and the Ebola optimization search algorithm. VBEOSA harnesses the collective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In addition, STRING analysis showed that dysregulated proteins belong to two clusters, centered on KDM5B, ATP5A1 and YAP1 and ERBB4. which are involved in proteosomes and tumorigenesis [87][88][89][90][91][92]. The altered expression of these proteins could underlie the synthetic lethal phenomenon exerted by LY2090314 treatment in a genetic environment with mutated cohesin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, STRING analysis showed that dysregulated proteins belong to two clusters, centered on KDM5B, ATP5A1 and YAP1 and ERBB4. which are involved in proteosomes and tumorigenesis [87][88][89][90][91][92]. The altered expression of these proteins could underlie the synthetic lethal phenomenon exerted by LY2090314 treatment in a genetic environment with mutated cohesin.…”
Section: Discussionmentioning
confidence: 99%